Custom WordPress Plugin for Native-Like Digital Health Literacy Questionnaires: Supporting the ALSATION Study - Ștefan SECRIERU (Applied Medical Informatics)
Health Literacy (HL) is a significant part of how people find and utilize health-related information. It refers to how people understand and make use of medical information in their lives. Moving into the digital era, health literacy has developed another crucial aspect: understanding, finding, and making informed decisions based on medical data and information found online. With this in mind, the World Health Organization designed four questionnaires for measuring digital health literacy in Europe. The ALSATION research team aimed to translate and culturally adapt the questionnaires into Romanian in seven steps [1]. The last three steps required a way to disseminate the translated versions to users in a non-biased and accessible manner. This study described how a custom plugin was employed to preserve the tabular structure and overall form’s look and feel, ensuring an authentic questionnaire experience. This allowed users (step seven and six) and experts (step five) to evaluate the clarity and necessity of each form item and provide further recommendations. To the best of the author’s knowledge, no existing plugins or third-party solutions allow for such a customized form. As a result, users can evaluate the translated questionnaires at any time in a clear and almost native-like questionnaire experience through the official webpage of the study [2].